Обогащение Словарного Запаса Младших Школьников - М.Ф.Давлетмухаметова (Periodica Journal, 2022)
Развитие речи — актуальная задача обучения в начальной школе. Речь выполняет функции общения, эмоционального самовыражения человека и воздействия на других людей. В статье рассмотрены методы обогащения словарного запаса, а также предоставлены результаты эффективности данных методик. Development is an urgent task of primary school education. Speech performs the functions of communication, emotional selfexpression of a person and influence on other people. The article discusses the methods of vocabulary enrichment, as well as the results of the effectiveness of these methods.
Keywords: Speech Developmen; Vocabulary; effectiveness; enrichment